OPERATION OF ELECTRIC MACHINES. TESTING, STANDARDS AND SIZE OF TRANSFORMERS AFTER OVERHAUL. (World Economics and Finance Bulletin, 2023)
This article, we will discuss the operation of electric machines, testing and standards, and the size of transformers after overhaul
Keywords: Electric machines; Operation; Testing; Standards